THE ROLE OF WOMEN’S LEADERSHIP, WORK FACILITIES AND EMOTIONAL INTELLIGENCE ON EMPLOYEE PERFORMANCE - Krisna Setiawan, Deni; Andriani, Dewi (Universitas Islam Lamongan, 2024)
This study aims to determine the role of female leadership, work facilities, and emotional intelligence on employee performance atPT. Yanaprima Hastapersada Tbk. This study uses a quantitative approach. Sampling using probability sampling techniques, with the accidental sampling method. Accidental sampling with a total of 85 respondents from employees atPT. Yanaprima Hastapersada Tbk. Data collection techniques using questionnaires distributed through questionnaires. Data analysis techniques in this study using multiple linear regression analysis. Data processing in this study using SPSS 25 software program (statistical program for the social sciences). The results of the study showed that through partial tests obtained (1) the role of female leadership has a significant effect on employee performance. (2) work facilities have a significant effect on employee performance. (3) emotional intelligence has a significant effect on employee performance. Based on the results of simultaneous testing (f test) shows that female leadership, work facilities, and emotional intelligence have an effect on employee performance.